Pengaruh Operating Capacity, Rasio Hutang, Dan Gender Diversity Terhadap Financial Distress Pada Masa Pandemi Covid-19 - Dura, Justita; Deva, Mutiara (Akuisisi : Jurnal Akuntansi, 2023)
The purpose of the study is to test the effect of operating capacity, debt ratio, and gender diversity on the financial distress conditions of hotel, restaurant, and tourism sub-sector companies listed on the IDX for the 2019-2021 period. The study used purposive sampling for sampling with a total sample of 10 companies from a total population of 42 companies. The theoretical foundation of the research uses signal theory and agency theory. From the research conducted, the results were obtained that operating capacity and debt ratio affect the company's financial distress condition, while gender diversity does not influence the company's financial distress condition. Advice for researchers is to choose other sectors and other variables that are likely to affect the company's financial distress.